Optically Induced Picosecond Lattice Compression in the Dielectric Component of a Strongly Coupled Ferroelectric/Dielectric Superlattice. (28th December 2021) - Sri Gyan, Deepankar; Lee, Hyeon Jun; Ahn, Youngjun; Carson, River B.; Carnis, Jerome; Kim, Tae Yeon; Unithrattil, Sanjith; Lee, Jun Young; Chun, Sae Hwan; Kim, Sunam; Eom, Intae; Kim, Minseok; et al.
Abstract: Above‐bandgap femtosecond optical excitation of a ferroelectric/dielectric BaTiO3 /CaTiO3 superlattice leads to structural responses that are a consequence of the screening of the strong electrostatic coupling between the component layers. Time‐resolved X‐ray free‐electron laser diffraction shows that the structural response to optical excitation includes a net lattice expansion of the superlattice consistent with depolarization‐field screening driven by the photoexcited charge carriers. The depolarization‐field‐screening‐driven expansion is separate from a photoacoustic pulse launched from the bottom electrode on which the superlattice is epitaxially grown. The distribution of diffracted intensity of superlattice X‐ray reflections indicates that the depolarization‐field‐screening‐induced strain includes a photoinduced expansion in the ferroelectric BaTiO3 and a contraction in CaTiO3 . The magnitude of expansion in BaTiO3 layers is larger than the contraction in CaTiO3 . The difference in the magnitude of depolarization‐field‐screening‐driven strain in the BaTiO3 and CaTiO3 components can arise from the contribution of the oxygen octahedral rotation patterns at the BaTiO3 /CaTiO3 interfaces to the polarization of CaTiO3 . The depolarization‐field‐screening‐driven polarization reduction in the CaTiO3 layers points to a new direction for the manipulation of polarization in the component layers of a strongly coupled ferroelectric/dielectric superlattice. Abstract : Optical excitation screens the strong electrostatic coupling between the component layers of a ferroelectric/dielectric BaTiO3 /CaTiO3 superlattice. The structural response to optical excitation includes a net lattice expansion consisting of the sum of expansion in ferroelectric BaTiO3 and contraction in CaTiO3 . The depolarization‐field‐screening‐driven polarization reduction in CaTiO3 points to new directions for the manipulation of nanoscale polarization.